2019
DOI: 10.1097/md.0000000000014933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of receptor activator nuclear factor κB gene polymorphisms on the susceptibility to knee osteoarthritis

Abstract: The present study aimed to explore genetic association of receptor activator nuclear factor κB (RANK) polymorphisms with individual susceptibility to knee osteoarthritis (OA) in different Kellgren–Lawrence (KL) grades. This case–control study included 138 knee OA patients and 145 healthy individuals. RANK rs1805034 and rs8086340 polymorphisms were genotyped through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The effects of RANK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The exonic SNP rs1805034C>T represents a nonsynonymous alanine ( C ) to valine ( T ) amino acid change (Ala192Val). The C variant was associated with susceptibility to Paget's disease of bone and knee osteoarthritis; conversely, it was found to have a protective role in hip osteoporotic fractures 26–28 . rs1805034 C was also a risk factor in esophageal cancer, but was not associated with risk for breast cancer 22,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…The exonic SNP rs1805034C>T represents a nonsynonymous alanine ( C ) to valine ( T ) amino acid change (Ala192Val). The C variant was associated with susceptibility to Paget's disease of bone and knee osteoarthritis; conversely, it was found to have a protective role in hip osteoporotic fractures 26–28 . rs1805034 C was also a risk factor in esophageal cancer, but was not associated with risk for breast cancer 22,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study of Yang et al ( 2019 ) documented that RANKL rs2277438 polymorphism increased RA risk, and that the RANK rs1805034 SNP was not related to RA risk. On the other hand, Wang et al ( 2019 ) found the RANK rs1805034 SNP to be associated with susceptibility to knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of chosen RANK and RANKL single nucleotide polymorphisms (SNPs) have been described before. The role of RANK rs1805034 polymorphism has been analyzed in regard to RA (Mohamed et al 2016 ; Yang et al 2019 ), cancer (Yin et al 2014 ; Zhang et al 2015 ), hip osteoporotic fractures (Zhang et al 2011 ), knee osteoarthritis (Wang et al 2019 ), age at menarche (Duan et al 2015 ; Pan et al 2012 ) and in Paget’s disease (Chung et al 2010 ). The RANK rs8086340 was also previously documented in RA patients, as well as with respect to age at natural menopause (Lu et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, after multivariate analysis, the polymorphism rs8086340 of the RANK gene was associated with the loss of orthodontic MIs. This polymorphism is located in the intron 1 and could have no functional effect on RANK , but it may play a role in the regulation of gene transcription or it may be in LD with other SNPs with potential functional effects . In addition, the C allele of this same polymorphism has also been shown associated with the anticitrullinated peptide antibody present in rheumatoid arthritis in the study of Ruyssen et al…”
Section: Discussionmentioning
confidence: 99%
“…RANK is a type I transmembrane glycoprotein, generally abundant in osteoclasts and cartilaginous cells, whose gene RANK is located on chromosome 18 in the 18q22.1 region. In addition, it is composed of 12 exons, with an extension of about 80 kb…”
Section: Introductionmentioning
confidence: 99%